FAKTOR PENGARUH TERHADAP KETERSEDIAAN SEPTICTANKDAN SAMBUNGAN SEWERAGE SYSTEM PERMUKIMAN PINGGIRAN KALI, KEL. DANGIN PURI, DENPASAR - dewa gede swastika; Utami Dwipayanti (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2012)
At dangin puri, sub distric of denpasar timur, most of communities that live at streamside donot have basic sanitation facilities such as septic tank or sewerage system connection, thus thewastewater is directly ? owed into the stream. This study was aimed to identify the risk factors thatin? uence septic tank ownership and sewerage facilities utilization by streamside communitiesin dangin puri. Some risk factors included in this study were knowledge, education, income,occupant density, house ownership, house position towards the stream, distance of toilet tostream and backyard size. The study was a cross-sectional study where the samples were familiesthat live at the streamside in dangin puri. Data were analyzed using logistic regression in order toidentify the most in? uencing factor of septic tank ownership and sewerage facilities utilization. The results illustrate that only one factor that proves the correlation that is distance of toiletto stream (or=8,733; p=0.006; ?=0.05), whereas other factors do not role as risk factors. Thecommunities with short distance of toilet to stream have a potential of 8.733 times to not have septictank and sewerage system connection compare to others. The data analysis also demonstratesthat there are other factors other than that included in this study with more in? uencing roles. Theregulation and the participation of all stakeholders such as communities and private sectors willimprove the coverage of basic sanitation in order to achieve the target of MDGs.